"One day it will be you who tells us doctors what to do!". Exploring the "Personal" of PHR in paediatric diabetes management. Issue 4 (28th October 2014) - Maria Piras, Enrico; Zanutto, Alberto
Abstract : Purpose: – Personal Health Record (PHR) systems make possible to integrate data from different sources and circulate them within the illness care and management network. The new arrangements prefigure a redefinition of the relations among healthcare practitioners, patients, and caregivers. The purpose of this paper is to consider the role and the meanings attributed to information when a technical artifact enables new forms of communication within the healthcare management network. Design/methodology/approach: – The authors adopted a qualitative research design, conducting a pre-post analysis on a theoretical sample of patients and of a paediatrics department. The authors selected 12 patients (six females and six males) aged between four and 20 years old. Findings: – The patients were willing to act as "stewards of their own information" (Halamka et al., 2008), but they interpreted this role in terms of restricting access to their information, rather than facilitating its dissemination. In fact, the PHR was symbolized as an instrument to support personal diabetes management but the patients want to preserve their own competence and independent management on the information regarding their "Personal" diseases. Originality/value: – This work highlights two connotation of "Personal" information. The first is the dimension of the right to the privacy of information when it is believed that it may be used to pass judgement on the patient. The second connotation of "Personal" is the assertion by patients of their competence and autonomy in interpreting the information on the basis of personal knowledge about their diabetes.